Dynamical localization of a thylakoid membrane binding protein is required for acquisition of photosynthetic competency. Issue 1 (12th February 2018) - Gutu, Andrian; Chang, Frederick; O'Shea, Erin K.
Summary: Vipp1 is highly conserved and essential for photosynthesis, but its function is unclear as it does not participate directly in light‐dependent reactions. We analyzed Vipp1 localization in live cyanobacterial cells and show that Vipp1 is highly dynamic, continuously exchanging between a diffuse fraction that is uniformly distributed throughout the cell and a punctate fraction that is concentrated at high curvature regions of the thylakoid located at the cell periphery. Experimentally perturbing the spatial distribution of Vipp1 by relocalizing it to the nucleoid causes a severe growth defect during the transition from non‐photosynthetic (dark) to photosynthetic (light) growth. However, the same perturbation of Vipp1 in dark alone or light alone growth conditions causes no growth or thylakoid morphology defects. We propose that the punctuated dynamics of Vipp1 at the cell periphery in regions of high thylakoid curvature enable acquisition of photosynthetic competency, perhaps by facilitating biogenesis of photosynthetic complexes involved in light‐dependent reactions of photosynthesis. Abstract : In live and growing cyanobacterial cells, cytosolic Vipp1 continuously concentrates on and off at regions of high thylakoid curvature. These punctuated dynamics of Vipp1 represent events of Vipp1 oligomerization on the thylakoid membrane which are essential for turning on photosynthetic metabolism, perhaps by mediating functional assembly of photosynthetic machinery.